The Application of Sayyidah ‘A’ishah’s Pedagogy in Islamic Education: A Field Study on Gender Justice at Pesantren in Madura - Ghofur, Abdul; Salama, Nadiatus; Ramdhan, Tri Wahyudi; Mukminin, Moh. Amiril (UIN Sunan Kudus, 2025)
This study aims to investigate the application of Sayyidah ‘Ā’ishah’s emancipatory pedagogy in contemporary Islamic education, with a focus on gender-inclusive educational models implemented in Pesantren (Islamic boarding schools) and Madrasah (Islamic schools) in Indonesia. The primary research question explores how the pedagogical principles exemplified by Sayyidah ‘Ā’ishah, such as dialogical teaching, intellectual courage, and constructive critique of religious text interpretations, are integrated into modern Islamic educational practices. Employing a qualitative, field-based methodology, data was collected through in-depth interviews with educators and students, classroom observations, and an analysis of relevant curriculum documents implemented in Pesantren and Madrasah. The findings reveal that while Sayyidah ‘Ā’ishah’s legacy provides a powerful model for promoting gender justice within Islamic education, its application faces various challenges, including resistance from some conservative educational structures. This research asserts that Sayyidah ‘Ā’ishah’s pedagogical model offers a feasible framework for reforming Islamic education, providing a path towards gender equity and intellectual liberation, while promoting critical thinking within Islamic educational institutions.